CONTACT TOXICITY OF DECAMETHRIN AND PERMETHRIN ON BLACK BEAN APHID AND TWO OF ITS COCCINELLID PREDATORS - Vasquez, Erlinda A.; Bernardo , Emiliana N.; Cariño, Ma. Flerida A. (Annals of Tropical Research, 1987)
The contact toxicity of decamethrin and permethrin was evaluated on adult black bean aphids. (Aphis craccivora Koch) and third instar larvae and adults of its coccinellid predators. Chilomenes sexmaculata Fabr. and Coleophora inaequalis Fabr. Based on LC50, decamethrin is more toxic to the black bean aphid than permethrin particularly after 48 hours exposure. The third instar larvae of C. inaequalis exhibited higher LC50 than C. sexmaculata at 24 hours but not after 48 hours of exposure to decamethrin. However, the latter species was more tolerant to permethrin than the former as indicated by the lower LC50 obtained in C. inaequalis. The LC50 values of the two insecticides were consistently lower for adults of C. sexmaculata than C. inaequalis at both exposure periods. The two insecticides used were more toxic to the aphids than to the coccinellid predators. Hence, they could be used to control aphids without adversely affecting the coccinellids which could also be utilized as biocontrol agents.